RELATIONSHIP BETWEEN TIDAL FORESTS (MANGROVES) AND COMMERCIAL SHRIMP PRODUCTION IN INDONESIA - Naamin, Nurzali (Marine Research in Indonesia, 1977)
An attempt has been made to relate the surface areas of tidal forest (mangrove) and the commercial shrimp production in those areas and adjacent waters in Indonesia. A significant linear relationship (a = 0.01) was obtained between these two variables as expressed in an equation : Y = 5.473 + 0.1128 X, where Y k the shrimp production in 103 tons and X is the mangrove surface area in 104 Ha. This relationship indicates that the shrimp production increases with the size of the tidal forest area implying that any reduction of the tidal forests, e.g. for industrial and agricultural purposes will cause a decrease in shrimp yield.